A retrospective analysis of neoadjuvant platinum-based chemotherapy versus up-front surgery in advanced ovarian cancer. (1st January 2006) - Steed, H.; Oza, A. M.; Murphy, J.; Laframboise, S.; Lockwood, G.; De Petrillo, D.; Sturgeon, J.; Rosen, B.
Abstract : The objective of this study is to compare progression-free survival (PFS) and overall survival (OS) of ovarian cancer patients treated with neoadjuvant chemotherapy and surgery to primary surgery and postoperative chemotherapy. Retrospective analysis from 1998 to 2003 of 116 patients with ovarian cancer was performed. Fifty women diagnosed by positive cytology received three cycles of carboplatin and paclitaxel. Thirty-six patients subsequently underwent cytoreductive surgery and completed three further cycles postoperatively. The OS and PFS were compared in 66 women treated with primary surgery and postoperative chemotherapy. A statistically significant difference was observed for OS ( P = 0.03, HR = 1.85, CI = 1.06–3.23) and PFS ( P = 0.04, HR = 1.61, CI = 1.03–2.53) favoring the primary surgery group. Due to the small numbers, age, grade, stage, pleural effusions, and histologic cell type were controlled for separately in the bivariate analyses. Controlling for stage made the results weaker. A matched subgroup survival analysis was performed on patients who had surgery following neoadjuvant chemotherapy. After matching for stage and grade and controlling age and pleural effusions ( N = 28 matched pairs), there was no statistical difference for OS ( P = 0.95, HR = 1.04, CI = 0.33–3.30) or PFS ( P = 0.79, HR = 1.11, CI = 0.98–1.04). It is concluded that primary surgery should be considered in all patients. Neoadjuvant chemotherapy may be an alternative in a subset of women with the intent to also perform interval debulking.